PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Pada Guru Di Yayasan Pendidikan Dan Kesejahteraan Sosial Maslakul Huda Sluke ) - Puji Santoso, 1342020020 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze whether job satisfaction had mediating effect of competencies and compensation on teacher performance in Yayasan Pendidikan dan Kesejahteraan Sosial Maslakul Huda Sluke. Sampling was done by census method so that all teachers who have civil servants who work in Yayasan Pendidikan dan Kesejahteraan Sosial Maslakul Huda Sluke, amounting to 82 people serve as respondents. Mechanical testing of the data used in this study include testing the validity of the factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, the coefficient of determination and significance t test to prove the hypothesis of the research and path analysis. The results showed that; competence and compensation has a significant positive effect on job satisfaction; competence, compensation and job satisfaction has a significant positive effect on teachers performance; job satisfaction able to mediated the influence of competence and compensation on teachers performance in Yayasan Pendidikan dan Kesejahteraan Sosial Maslakul Huda Sluke. Keywords:Â competence, compensation, job satisfaction, teacher performance